2012
DOI: 10.1038/onc.2011.606
|View full text |Cite
|
Sign up to set email alerts
|

A Notch1–neuregulin1 autocrine signaling loop contributes to melanoma growth

Abstract: The Notch pathway is an evolutionary conserved signaling cascade that has an essential role in melanoblast and melanocyte stem cell homeostasis. Notch signaling is emerging as a key player in melanoma, the most deadly form of skin cancer. In melanoma, Notch1 is inappropriately reactivated and contributes to melanoma tumorigenicity. Here, we propose a novel mechanism by which Notch1 promotes the disease. We found that Notch1 directly regulates the transcription of neuregulin1 (NRG1) by binding to its promoter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 52 publications
3
52
0
Order By: Relevance
“…5B). Expression of active Notch1 conferred growth advantages as described previously (6), in both control and shMT1-MMP-expressing cells, suggesting that reconstitution of Notch1 signaling can, at least in part, restore cell growth that is inhibited by MT1-MMP knockdown. Conversely, WM115 cells expressing active MT1-MMP were transduced with a specific shRNA against Notch1 (Fig.…”
Section: Mt1-mmp Activation Of Notch1mentioning
confidence: 88%
See 4 more Smart Citations
“…5B). Expression of active Notch1 conferred growth advantages as described previously (6), in both control and shMT1-MMP-expressing cells, suggesting that reconstitution of Notch1 signaling can, at least in part, restore cell growth that is inhibited by MT1-MMP knockdown. Conversely, WM115 cells expressing active MT1-MMP were transduced with a specific shRNA against Notch1 (Fig.…”
Section: Mt1-mmp Activation Of Notch1mentioning
confidence: 88%
“…Notch1 is an essential embryonic stem cell factor that plays key roles in the maintenance of melanocyte/melanoma precursor cell homeostasis (4). We have previously demonstrated that although in mature melanocytes the levels of Notch1 are low or undetectable, melanomas re-express Notch1, and active Notch1 is required for their growth and survival (5,6). However, unlike T-cell lymphoblastic leukemia, melanomas do not present activating mutations in the Notch1 gene (7), suggesting that Notch1 activation occurs via other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations